2013
DOI: 10.1038/cddis.2013.223
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin induces cell death via inactivation of Stat3 and downregulation of Skp2

Abstract: Salinomycin has been shown to control breast cancer stem cells, although the mechanisms underlying its anticancer effects are not clear. Deregulation of cell cycle regulators play critical roles in tumorigenesis, and they have been considered as anticancer targets. In this study, we investigated salinomycin effect on cell cycle progression using OVCAR-8 ovarian cancer cell line and multidrug-resistant NCI/ADR-RES and DXR cell lines that are derived from OVCAR-8. Parental OVCAR-8 cells are sensitive to several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 54 publications
(95 reference statements)
2
42
0
Order By: Relevance
“…Caspase-independent apoptosis was postulated by Fuchs and colleagues who demonstrated that salinomycin activates a distinct apoptotic pathway, which was not accompanied by cell cycle arrest and that was independent from the tumor suppressor protein p53, caspase activation, and the CD95/CD95L system (Fuchs et al, 2009). There is also a report on cell death induction via inactivation of Stat 3 (Koo et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Caspase-independent apoptosis was postulated by Fuchs and colleagues who demonstrated that salinomycin activates a distinct apoptotic pathway, which was not accompanied by cell cycle arrest and that was independent from the tumor suppressor protein p53, caspase activation, and the CD95/CD95L system (Fuchs et al, 2009). There is also a report on cell death induction via inactivation of Stat 3 (Koo et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Both have been shown to induce cell death via apoptotic and autophagic pathways (57-59). Moreover, the HDAC inhibitors have also been shown to induce dedifferentiation, and in so doing reduce tumor growth and metastasis (60).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of cell proliferation by blocking the G1 to S transition was also observed, as was downregulation of the levels of phosphorylated Cyclin E (Thr62) and p27Kip1 (Thr187). Furthermore, another small molecule, Salinomycin, inhibited STAT3 activity and thus decreased expression of Stat3-target genes including Skp2 [ 78 ]. Salinomycin was found to induce degradation of Skp2, accompanied by p27 accumulation, cell cycle arrest, and apoptosis.…”
Section: Skp2 As a Potential Therapeutic Target For Cancermentioning
confidence: 99%